Crafting modernism - Hill, Kerry; London, Geoffrey; Finch, Paul, 1949-; Viray, Erwin; Riera Ojeda, Oscar (London : Thames & Hudson, 2013)
Crafting Modernism is a long overdue book that examines and celebrates more than 30 years of consistently strong and innovative work by Kerry Hill Architects, an architectural studio with offices in Singapore and Fremantle, Australia. This multi-award winning practice established its reputation with a series of exotic resorts in locations throughout South-East Asia. It also designed a brace of exceptional houses that were informed by the earlier resort work. Organised chronologically, this four hundred page book features an extended essay about the evolution of practise and a selection of forty of Kerry Hill's most important works from 1992 - 2012. This gives readers privileged view into the world and thinking of an architectural practice that richly deserves international exposure.
Includes bibliographical references.
Keywords: Kerry Hill Architects (Firm).; Architectural firms -- History; Architect-designed houses -- Pictorial works; Architecture -- 20th century -- Pictorial works; Architecture -- 21st century -- Pictorial works